Cold Extraction of Phyllanthus Niruri, Chromolaena Oodorata, Melastoma Malabathricum & Azadirachta Indica Plants Via High-Pressure Processing (HPP): Evaluation of Physiochemical Properties and Antioxidant Activity - Ibrahim, Fatihah; Mohd Fauzi, Noor Akhmazillah; Razali, Faiz (Progress in Engineering Application and Technology, 2023)
Phyllanthus niruri, Chromolaena odorata, Melastoma malabtahricum, and Azdirachta indica are among hundreds of medicinal plants in the world. These plants have been used for many medicinal purposes since decades ago due to their bioactive compounds. The extraction method is critical in displaying the biological features of therapeutic plants in which the recovered compounds can be applied to various products in food, cosmeceutical, dietary, and other health-related products. Traditional extraction which involves boiling at high temperature can result in the loss of some bioactive compound including phenolic compound who contribute to the antioxidant activity due to denaturation caused by heat. Therefore, as an alternative, High-Pressure Processing (HPP) was employed as to minimize any quality denaturation during processing. HPP was carried out at two (2) different pressures (200 and 600 MPa) with three (3) different holding times (5, 10, and 15 minutes) respectively. Traditional method at boiling temperature of water (100ºC) for 30 minutes was also carried out as a comparison. The samples were analyzed in terms on its physiochemical properties (pH and color), antioxidant activity, and total phenolic content (TPC). HPP-treated of A. indica plant extract exhibits the highest antioxidant activity at 600 MPa/10 min registered 88.55 ± 0.04 % scavenging activities whilst the highest TPC was observed to be HPP-treated of A. indica at 200MPa/5min. Based on the results obtained, it can be concluded that HPP was able to extract bioactive compound as shown by the substantial amount of antioxidant activity obtained from all plants extract of P. niruri, C. odorata, A. indica, and M. malabathricum.